Zervixkarzinom in der Schwangerschaft = Cervical cancer in pregnancy - Au, Alexandra von; Schneeweiss, Andreas; Seitz, Julia; Sohn, Christof; Rom, Joachim; Marmé, Frederik (Der Onkologe, 2018)
BackgroundCervical cancer is the most common gynecological cancer diagnosed during pregnancy. Because a guideline-conform treatment analogous to the treatment of non-pregnant women would, in most cases, not be compatible with preserving a pregnancy, after interdisciplinary discussion of the case the planning of an individual treatment concept taking the patients will into consideration, is of central importance.ResultsTreatment is principally determined by the FIGO (International Federation of Gynecology and Obstetrics) stage of the disease, the nodal status and two additional factors: gestational age and the patient’s desire to preserve the pregnancy or fertility. While in the case of abnormal cervical screening results diagnostic procedures, such as colposcopy and biopsy are possible at any time during pregnancy, the patient should not have surgery until the end of the first trimester. For a precise risk estimation as possible, laparoscopic staging of pelvic lymph nodes by lymphadenectomy is recommended from FIGO stage IB1 onwards. For higher FIGO stages neoadjuvant chemotherapy using a platinum-based regimen can be administered to preserve the pregnancy until fetal maturity is reached.ConclusionDespite the overall sparcity of current data, a preservation of the pregnancy seems to be possible in most cases without significant deterioration of the patient’s prognosis.